Paclitaxel, 5-fluorouracil, and leucovorin combination chemotherapy as first-line treatment in patients with advanced gastric cancer. Issue 3 (March 2019) - Que, Wan-Cai; Huang, Yan-Fang; Lin, Xiao-Yan; Lan, Yan-Qin; Gao, Xin-Yan; Wang, Xin-Li; Wu, Ri-Ping; Du, Bin; Huang, Xiao-Bin; Qiu, Hong-qiang; Zhong, Dong-Ta
Abstract : The aim of this retrospective analysis was to evaluate the efficacy and toxicity of combination chemotherapy with paclitaxel, 5-fluorouracil, and leucovorin (TFL) as first-line treatment in patients with advanced gastric cancer (AGC). One hundred and thirteen patients were enrolled in the study who were confirmed to have AGC by histopathology. These patients were treated with TFL: paclitaxel at a dose of 135 mg/m 2 as a 3-h intravenous infusion on day 1, LV 400 mg/m 2 as an intravenous infusion over 2 h on day 1, followed by 5-fluorouracil 2400 mg/m 2 as an infusion over a 46-h period on 3 consecutive days. Cycles were repeated every 2 weeks. A total of 113 patients were assessed for their response to therapy. A total of three patients achieved complete responses and 46 patients achieved partial responses, yielding an overall objective response rate of 43.4% [95% confidence interval (CI): 34.3–52.5%]. Fifty-four cases of stable disease and 10 cases of progressive disease were observed in the remaining patients. The median time to progression and overall survival were 5.2 months (95% CI: 4.7–5.8 months) and 14.1 months (95% CI: 12.5–15.8 months), respectively. Toxicities were tolerable and moderate. The most common grade 3–4 toxicities included leukopenia (16.8%), neutropenia (17.7%), anemia (8.0%), thrombocytopenia (5.3%), and fatigue (6.2%). Combination chemotherapy with TFL offers an active and safe therapeutic approach for patients with AGC.